Electrode active material particles, electrode composite material, and lithium ion battery
By adding amorphous silicon part to the silicon inclusion electrode active material particles to control its proportion to improve ionic conductivity, the problem of expansion of the silicon inclusion electrode active material during charging is solved, and the performance of lithium-ion batteries is significantly improved .
Patent Information
- Application Number
- CN202410642672.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-07-28
- Filing Date
- 2024-05-23
- Publication Date
- 2025-02-14
AI Technical Summary
The expansion of the silicon inclusion electrode active material during charging still needs to be further suppressed.
By adding amorphous silicon part to the electrode active material particles and controlling its proportions, it satisfies a specific atomic percentage range, thereby improving the ionic conductivity of the particles and preventing expansion caused by uneven reactions.
It effectively suppresses the expansion of electrode active material particles during charging, and improves the performance of lithium-ion batteries.
Smart Images

Figure CN119447214A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to electrode active material particles, electrode composite materials and lithium ion batteries Background Art
[0002] In recent years, the development of batteries has been actively carried out. For example, in the automotive industry, the development of batteries used in electric vehicles or hybrid vehicles is advancing. In addition, silicon is known as an electrode active material used in batteries, especially lithium-ion batteries.
[0003] Silicon electrode active materials have a large theoretical capacity and are effective for increasing the energy density of batteries. However, silicon electrode active materials have a problem of large expansion during charging. In response to this, it is known that silicon clathrate electrode active materials can be used as silicon electrode active materials to suppress expansion during charging.
[0004] For example, Japanese Patent Application Laid-Open No. 2021-158003 discloses a silicon inclusion compound electrode active material having a silicon inclusion compound II type crystal phase and having Na x Si 136 (1.98<x<2.54) composition. Summary of the invention
[0005] Silicon inclusion compound electrode active materials can suppress expansion during charge compared to ordinary silicon electrode active materials, but there is still a need to further suppress expansion of silicon inclusion compound electrode active materials during charge.
[0006] An object of the present disclosure is to provide electrode active material particles that expand less during charge and a lithium ion battery having such electrode active material particles.
[0007] The inventors of the present application have found that the above-mentioned problems can be solved by the following means.
[0008] <Scheme 1>
[0009] The electrode active material particle comprises a silicon inclusion compound part and an amorphous silicon part, and satisfies the following relationship:
[0010] 0 atomic %<the number of silicon atoms in the amorphous silicon portion / (the number of silicon atoms in the amorphous silicon portion+the number of silicon atoms in the silicon inclusion compound portion)<50 atomic %.
[0011] <Scheme 2>
[0012] The electrode active material particles according to Scheme 1 satisfy the following relationship:
[0013] 0 atomic %<the number of silicon atoms in the amorphous silicon portion / (the number of silicon atoms in the amorphous silicon portion+the number of silicon atoms in the silicon inclusion compound portion)≤30 atomic %.
[0014] <Scheme 3>
[0015] An electrode composite material comprising the electrode active material particles described in Scheme 1 or 2.
[0016] <Scheme 4>
[0017] A lithium-ion battery having an electrode active material layer, wherein the electrode active material layer contains the electrode composite material described in Scheme 3.
[0018] According to the present disclosure, it is possible to provide electrode active material particles that expand less during charging and a lithium ion battery having such electrode active material particles. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Features, advantages, and technical and industrial significance of exemplary embodiments of the present invention will be described below with reference to the accompanying drawings, wherein like reference numerals represent like elements, and wherein:
[0020] Figure 1 This is a cross-sectional TEM image of the electrode active material particle disclosed in the present invention. DETAILED DESCRIPTION
[0021] The following is a detailed description of the embodiments of the present disclosure. Note that the present disclosure is not limited to the following embodiments, and can be implemented with various modifications within the scope of the disclosed gist.
[0022] 《Electrode Active Material Particles》
[0023] The electrode active material particles disclosed herein contain a silicon inclusion compound portion and an amorphous silicon portion, and satisfy the following relationship:
[0024] 0 atomic %<the number of silicon atoms in the amorphous silicon portion / (the number of silicon atoms in the amorphous silicon portion+the number of silicon atoms in the silicon inclusion compound portion)<50 atomic %.
[0025] The change in expansion rate caused by charging and discharging of silicon inclusion particles is small, but the silicon inclusion particles are highly sensitive to uneven reactions (uneven reactions), and the expansion rate increases due to the uneven progress (occurrence and deepening) of the reactions. In this regard, the inventors of the present application believe that the low ionic conductivity of the silicon inclusion particles is the cause of the uneven reaction. Specifically, without intending to be bound by any theory, it is believed that since the ionic conductivity of the silicon inclusion is low, the reaction is concentrated on the particle surface, and thus the reaction proceeds (occurs and deepens) unevenly.
[0026] In view of this, the inventors of the present application have found that by making the silicon electrode active material particles contain a silicon inclusion compound portion and an amorphous silicon portion with high ion conductivity, it is possible to prevent the reaction from proceeding unevenly (occurring and deepening) within the active material particles, thereby suppressing an increase in the expansion rate.
[0027] In addition, regarding the present disclosure, the “electrode active material” can be used as a “positive electrode active material” or a “negative electrode active material”, and can be used as a “negative electrode active material” in particular.
[0028] The electrode active material particles disclosed herein include a silicon inclusion compound portion and an amorphous silicon portion.
[0029] The electrode active material particles disclosed in the present invention satisfy the following relationship:
[0030] 0 atomic %<the number of silicon atoms in the amorphous silicon portion / (the number of silicon atoms in the amorphous silicon portion+the number of silicon atoms in the silicon inclusion compound portion)<50 atomic %.
[0031] The number of silicon atoms in the amorphous silicon part / (the number of silicon atoms in the amorphous silicon part + the number of silicon atoms in the silicon inclusion compound part) may be greater than 0.10 atomic %, greater than 0.30 atomic %, greater than 0.50 atomic %, greater than 0.70 atomic %, greater than 0.80 atomic %, greater than 0.90 atomic %, or greater than 0.95 atomic %, and may be less than 45 atomic %, less than 40 atomic %, less than 35 atomic %, less than 30 atomic %, less than 25 atomic %, less than 20 atomic %, less than 15 atomic %, less than 10 atomic %, less than 5.0 atomic %, less than 3.0 atomic %, or less than 1.0 atomic %.
[0032] As a method for quantifying the silicon inclusion compound part and the amorphous silicon part in the electrode active material particles, a method using a crystal orientation analysis system (ASTAR) attached to a transmission electron microscope (TEM) can be cited. More specifically, using ASTAR of Nanomegas, while scanning the sample with an electron beam probe, while continuously collecting diffraction patterns, it is possible to quantify the silicon inclusion compound part and the amorphous silicon part in the electrode active material particles.
[0033] The ionic conductivity of the electrode active material particles may be greater than 0.066 mS / cm. Alternatively, the ionic conductivity may be greater than 0.067 mS / cm, greater than 0.068 mS / cm, or greater than 0.069 mS / cm, and less than 0.100 mS / cm, less than 0.090 mS / cm, less than 0.085 mS / cm, or less than 0.080 mS / cm.
[0034] The ionic conductivity can be measured by the following method. That is, first, the electrode active material particles are pressed and a restraining pressure is applied to the obtained pressed tablet. Then, the ionic conductivity is calculated by the AC impedance method while the obtained sample is kept at 25°C. The measurement can be performed using Solartron 1260 from Solartron Analytical. The measurement conditions can be set to an applied voltage of 5mV and a measurement frequency range of 0.01 to 1MHz.
[0035] As a method for manufacturing the electrode active material particles disclosed in the present invention, the following method can be exemplified, but is not limited thereto. The method comprises: mixing a silicon raw material and a sodium raw material and heating them to alloy them to obtain a powdered sodium silicon (NaSi) alloy; and mixing the obtained NaSi alloy and aluminum fluoride and heating them to form an inclusion compound to obtain a silicon inclusion compound.
[0036] As the sodium raw material in the alloying step, sodium hydride can be exemplified, but the present invention is not limited thereto.
[0037] The heating temperature in the alloying step may be 350°C or higher, 400°C or higher, or 450°C or higher, and may be 650°C or lower, 600°C or lower, or 550°C or lower.
[0038] The heating temperature in the inclusion compound formation step may be 200°C or higher, 250°C or higher, or 270°C or higher, and may be 400°C or lower, 350°C or lower, or 330°C or lower.
[0039] By adjusting the heating temperature in the alloying step and the inclusion step, and using aluminum fluoride of a specified particle size in the inclusion step, the ratio of the silicon inclusion compound part to the amorphous silicon part in the obtained electrode active material particles can be controlled. Furthermore, by charging the obtained electrode active material particles, the ratio can also be controlled.
[0040] The silicon inclusion compound in the electrode active material of the present disclosure may be a porous silicon inclusion compound. The porous silicon inclusion compound can absorb the expansion caused by charge and discharge by using its voids.
[0041] As a method for producing the electrode active material particles of the present disclosure when the silicon inclusion compound part is a porous silicon inclusion compound, the following method can be exemplified, but is not limited thereto. The method includes: mixing silicon and metallic lithium to obtain a lithium silicon (LiSi) alloy; reacting the obtained LiSi alloy with ethanol to obtain porous silicon; and using the obtained porous silicon as a silicon raw material to obtain a silicon inclusion compound as described above.
[0042] Electrode Composite Materials
[0043] The electrode composite material (electrode composite material) disclosed herein includes electrode active material particles and optionally contains a solid electrolyte, a conductive auxiliary agent, and a binder.
[0044] 〈Electrode active material particles〉
[0045] For the electrode active material particles, reference can be made to the above description related to the electrode active material particles of the present disclosure.
[0046] 〈Solid Electrolyte〉
[0047] The material of the solid electrolyte is not particularly limited, and any material that can be used as a solid electrolyte for lithium-ion batteries can be used. For example, the solid electrolyte may be a sulfide solid electrolyte.
[0048] Examples of sulfide solid electrolytes include, but are not limited to, sulfide amorphous solid electrolytes, sulfide crystalline solid electrolytes, and argyrodite-type solid electrolytes. Specific examples of sulfide solid electrolytes include Li2S-P2S5 (Li7P3S 11 , Li3PS4, Li8P2S9, etc.), Li2S-SiS2, LiI-Li2S-SiS2, LiI-Li2S-P2S5, LiI-LiBr-Li2S-P2S5, Li2S-P2S5-GeS2 (Li 13 GeP3S 16 , Li 10 GeP2S 12 etc.), LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, Li 7-x PS 6-x Cl x etc.; or combinations thereof, but not limited to these.
[0049] The sulfide solid electrolyte may be glass or crystallized glass (glass ceramic).
[0050] 〈Conductive additives〉
[0051] The conductive additive is not particularly limited and may be, for example, VGCF (vapor grown carbon fiber), acetylene black (AB), Ketjen black (KB), carbon nanotube (CNT), carbon nanofiber (CNF), etc., but is not limited thereto.
[0052] 〈Adhesives〉
[0053] The binder is not particularly limited, and may be, for example, polyvinylidene fluoride (PVDF), butadiene rubber (BR), styrene butadiene rubber (SBR), or a combination thereof, but is not limited thereto.
[0054] Furthermore, with respect to the present disclosure, "electrode composite material" refers to a composition that can directly constitute an electrode active material layer, or can constitute an electrode active material layer by further comprising other components. In addition, with respect to the present disclosure, "electrode composite material slurry" refers to a slurry that contains a dispersion medium in addition to the "electrode composite material" and can form an electrode active material layer by coating and drying the dispersion medium.
[0055] Lithium-ion battery
[0056] The lithium-ion battery of the present disclosure may be a liquid battery or a solid battery. In addition, with respect to the present disclosure, a "solid battery" refers to a battery that uses at least a solid electrolyte as an electrolyte, and therefore, a solid battery may use a combination of a solid electrolyte and a liquid electrolyte as an electrolyte. In addition, the solid battery of the present disclosure may be an all-solid battery, that is, a battery that uses only a solid electrolyte as an electrolyte.
[0057] The lithium ion battery of the present disclosure can be constrained from both sides of the stacking direction of each layer by constraining members such as end plates. As a constraining method, a method using the constraining torque of a bolt can be exemplified, but it is not limited to this.
[0058] The lithium ion battery of the present disclosure has an electrode active material layer, and the electrode active material layer contains the electrode composite material of the present disclosure. In particular, the negative electrode composite material of the lithium ion battery of the present disclosure may be the electrode composite material of the present disclosure, in which case the lithium ion battery may sequentially include a negative electrode collector layer, a negative electrode active material layer containing the electrode composite material of the present disclosure, a solid electrolyte layer, a positive electrode active material layer, and a positive electrode collector layer.
[0059] 〈Negative electrode current collector layer〉
[0060] The material used for the negative electrode collector layer is not particularly limited, and any material that can be used as a negative electrode collector for a battery can be appropriately adopted, such as copper, copper alloys, and products obtained by plating or vapor-depositing copper with nickel, chromium, carbon, etc., but is not limited to these.
[0061] The shape of the negative electrode current collector layer is not particularly limited, and examples thereof include a foil shape, a plate shape, a mesh shape, etc. Among them, a foil shape is preferred.
[0062] <Negative electrode active material layer>
[0063] The negative electrode active material layer contains the electrode composite material of the present disclosure. For the electrode composite material, reference can be made to the above description related to the electrode composite material of the present disclosure.
[0064] Furthermore, when the negative electrode active material layer contains a solid electrolyte, the mass ratio of the electrode active material particles to the solid electrolyte in the negative electrode active material layer (mass of the electrode active material particles:mass of the solid electrolyte) is preferably 85:15 to 30:70, and more preferably 80:20 to 40:60.
[0065] The thickness of the negative electrode active material layer can be, for example, 0.1 to 1000 μm.
[0066] 〈Solid electrolyte layer〉
[0067] The solid electrolyte layer contains at least a solid electrolyte. In addition, the solid electrolyte layer may contain a binder and the like as needed in addition to the solid electrolyte. For the solid electrolyte and the binder, reference may be made to the above description related to the electrode composite material disclosed in the present invention.
[0068] The thickness of the solid electrolyte layer is, for example, 0.1 to 300 μm, or preferably 0.1 to 100 μm.
[0069] <Positive electrode active material layer>
[0070] The positive electrode active material layer is a layer containing a positive electrode active material and, optionally, a solid electrolyte, a conductive auxiliary agent, a binder, a thickener, and the like.
[0071] There is no particular limitation on the material of the positive electrode active material. For example, the positive electrode active material may be lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMn2O4), LiCo 1 / 3 Ni 1 / 3 Mn 1 / 3 O2, by Li 1+x Mn 2-x-y M y O4 (M is one or more metal elements selected from Al, Mg, Co, Fe, Ni and Zn) is a heterogeneous element substituted Li-Mn spinel, lithium titanate (Li x TiO y ), lithium metal phosphate (LiMPO4, M is one or more metals selected from Fe, Mn, Co and Ni), etc., but is not limited to these.
[0072] The positive electrode active material may have a coating layer. The coating layer is a layer containing a material having lithium ion conductivity, low reactivity with the positive electrode active material and the solid electrolyte, and capable of maintaining a non-flowing coating layer even when in contact with the active material or the solid electrolyte. Specific examples of materials constituting the coating layer include Li4Ti5O 12 , Li3PO4, etc., but are not limited to these.
[0073] The shape of the positive electrode active material may be, for example, a particle shape. The average particle size (D50) of the positive electrode active material is not particularly limited, and may be, for example, 10 nm or more, or 100 nm or more. On the other hand, the average particle size (D50) of the positive electrode active material may be, for example, 50 μm or less, or 20 μm or less. The average particle size (D50) may be calculated, for example, by measurement using a laser diffraction particle size distribution meter or a scanning electron microscope (SEM).
[0074] For the solid electrolyte, the conductive auxiliary agent and the binder, reference may be made to the above description related to the electrode composite material of the present disclosure.
[0075] When the positive electrode active material layer contains a solid electrolyte, the mass ratio of the positive electrode active material to the solid electrolyte (mass of the positive electrode active material:mass of the solid electrolyte) in the positive electrode active material layer is preferably 85:15 to 30:70, more preferably 80:20 to 50:50.
[0076] The thickness of the positive electrode active material layer is, for example, 0.1 μm to 1000 μm, preferably 1 μm to 100 μm, and more preferably 30 μm to 100 μm.
[0077] 〈Positive electrode collector layer〉
[0078] There is no particular limitation on the material used in the positive electrode collector layer. Materials that can be used as positive electrode collectors for batteries can be appropriately used, such as SUS, nickel, chromium, gold, platinum, aluminum, iron, titanium, zinc, and products of plating or vapor-depositing these metals with nickel, chromium, carbon, etc., but are not limited to these.
[0079] The shape of the positive electrode current collector layer is not particularly limited, and examples thereof include a foil shape, a plate shape, a mesh shape, etc. Among them, a foil shape is preferred.
[0080] "Synthesis Example 1"
[0081] 〈Synthesis of Electrode Active Material Particles〉
[0082] (porous)
[0083] As a silicon (Si) source, Si powder (High Purity Science Research Institute, SIEPB32) was prepared. The Si powder and metallic lithium (Li) were weighed at a molar ratio of Li / Si=4.0, and the weighed Si powder and Li were mixed in a mortar in an argon atmosphere to obtain a lithium silicon (LiSi) alloy. The obtained LiSi alloy was reacted with ethanol in an argon atmosphere and treated with hydrogen fluoride (HF) to obtain a Si powder having voids inside the primary particles, that is, a Si powder having a porous structure.
[0084] (Alloying)
[0085] A sodium silicon (NaSi) alloy was manufactured using Si powder having a porous structure and sodium hydride (NaH) as a sodium (Na) source. As NaH, NaH previously washed with hexane was used. NaH and Si powder were weighed so that the molar ratio was 1.05:1, and the weighed NaH and Si powder having a porous structure were mixed using a cutting mill. The obtained mixture was heated in a heating furnace under an argon atmosphere at 500°C for 40 hours to obtain a powdered NaSi alloy.
[0086] (Inclusion Compound)
[0087] The obtained NaSi alloy and aluminum fluoride (AlF3) particles were weighed so that the molar ratio was 1:0.35, and the weighed NaSi alloy and AlF3 particles were mixed by a cutting mill to obtain a reaction raw material. The obtained powdered reaction raw material was placed in a stainless steel reaction container, heated in an argon atmosphere in a heating furnace at 310°C for 60 hours to react, thereby obtaining a silicon inclusion compound. The obtained silicon inclusion compound was acid-washed using a mixed solvent prepared by mixing HNO3 and H2O in a volume ratio of 10:90 to remove by-products in the reaction product. After washing, it was filtered, and the solid component separated by filtration was dried at 120°C for more than 3 hours to obtain a powdered silicon inclusion compound. The obtained silicon inclusion compound was then washed with a 3wt% hydrogen fluoride (HF) solution, filtered, and dried at 120°C for more than 3 hours to obtain the electrode active material particles of Synthesis Example 1.
[0088] 《Comparative Synthesis Example 1》
[0089] In the alloying step, Si powder (High Purity Science Research Institute, SIEPB32) was used, that is, porous silicon was not prepared before the alloying step; except for heating at 700°C for 20 hours, the same operation as Synthesis Example 1 was performed to obtain a NaSi alloy. The obtained NaSi alloy was heated at 340°C in an argon atmosphere in a heating furnace to form an inclusion compound, and then pulverized using a ball mill (manufactured by Freech), thereby obtaining the electrode active material particles of Comparative Synthesis Example 1.
[0090] 《Comparative Synthesis Example 2》
[0091] Metallic lithium (Li) and Si powder (High Purity Science Institute, SIEPB32) were weighed so that the molar ratio was 4:1, and mixed in a mortar under an argon atmosphere at room temperature for 0.5 hours to react them. Thus, Li4Si was obtained. The obtained Li4Si was reacted with ethanol under an argon atmosphere. The reaction product was filtered, and the solid component separated by filtration was dried at 120°C for more than 3 hours to obtain powdered porous silicon. The porous silicon was washed with a 3wt% HF solution, filtered, and dried at 120°C for more than 3 hours to obtain the electrode active material particles of Comparative Synthesis Example 2.
[0092] 《Comparative Synthesis Example 3》
[0093] Electrode active material particles of Comparative Synthesis Example 3 were obtained in the same manner as Synthesis Example 1 except that inclusion complex formation was carried out using AlF 3 pulverized by a ball mill.
[0094] In addition, the surface of the electrode active material particle of each example may include a film or impurities containing O element, C element, N element, etc.
[0095] 《Example 1》
[0096] 〈Manufacturing of lithium-ion batteries〉
[0097] (Preparation of negative electrode composite material)
[0098] In a polypropylene container, butyl butyrate, a 5wt% butyl butyrate solution of a polyvinylidene fluoride (PVDF)-based binder, vapor-grown carbon fiber (VGCF) as a conductive aid, the electrode active material particles of Synthesis Example 1, and Li2S-P2S5-based glass ceramics as a sulfide solid electrolyte were added, and stirred for 30 seconds using an ultrasonic dispersion device (UH-50 made by SMT). Next, the container was vibrated for 30 minutes using a vibrator (TTM-1 made by Shibata Science Co., Ltd.) to obtain a slurry-like negative electrode composite material (negative electrode composite material slurry).
[0099] (Formation of Negative Electrode Active Material Layer)
[0100] The obtained negative electrode composite material slurry was applied on a copper (Cu) foil as a negative electrode collector layer using a coater by a doctor blade method, and dried on a hot plate heated to 100° C. for 30 minutes to form a negative electrode active material layer on the negative electrode collector layer.
[0101] (Formation of Solid Electrolyte Layer)
[0102] Heptane, a 5 wt% heptane solution of a butene rubber (BR)-based binder, and Li2SP2S5-based glass ceramics as a sulfide solid electrolyte were added to a polypropylene container and stirred for 30 seconds using an ultrasonic dispersion device (UH-50 manufactured by SMT). Next, the container was vibrated for 30 minutes using a vibrator (TTM-1 manufactured by Shibata Science Co., Ltd.) to obtain a solid electrolyte slurry.
[0103] The obtained solid electrolyte slurry was applied onto an aluminum (Al) foil as a release sheet using a coater by a doctor blade method, and dried on a hot plate heated to 100° C. for 30 minutes to form a solid electrolyte layer. A plurality of solid electrolyte layers were produced.
[0104] (Preparation of positive electrode composite material)
[0105] In a polypropylene container, butyl butyrate, a 5 wt % butyl butyrate solution of a PVDF-based binder, and LiNi 2000 with an average particle size of 6 μm as a positive electrode active material were added. 1 / 3 Co 1 / 3 Mn 1 / 3 O2, Li2S-P2S5 glass ceramics as sulfide solid electrolyte, and VGCF as conductive additive were stirred for 30 seconds using an ultrasonic dispersion device (UH-50 manufactured by SMT). Next, the container was vibrated for 3 minutes using a vibrator (TTM-1 manufactured by Shibata Science Co., Ltd.), and then stirred for 30 seconds using an ultrasonic dispersion device and vibrated for 3 minutes using a vibrator to obtain a slurry-like positive electrode composite material (positive electrode composite material slurry).
[0106] (Formation of Positive Electrode Active Material Layer)
[0107] The obtained positive electrode composite material slurry was applied onto Al foil as a positive electrode collector layer using a doctor blade method using a coater and dried on a hot plate heated to 100° C. for 30 minutes to form a positive electrode active material layer on the positive electrode collector layer.
[0108] 〈Battery Assembly〉
[0109] The positive electrode current collector layer, the positive electrode active material layer, and the first solid electrolyte layer were stacked in this order, and the stack was placed in a roll press and pressed at a pressing pressure of 100 kN / cm and a pressing temperature of 165° C., thereby obtaining a positive electrode stack.
[0110] The negative electrode current collector layer, the negative electrode active material layer, and the second solid electrolyte layer were stacked in this order, and the stack was placed in a roll press and pressed at a pressing pressure of 60 kN / cm and a pressing temperature of 25° C., thereby obtaining a negative electrode stack.
[0111] Furthermore, the Al foil as a release sheet was released from the surfaces of the solid electrolyte layers of the positive electrode stack and the negative electrode stack. Next, the Al foil as a release sheet was released from the third solid electrolyte layer.
[0112] The solid electrolyte layers of the positive electrode stack and the negative electrode stack were stacked one on top of the other, with the solid electrolyte layers facing each other, and the stack was placed in a flat uniaxial press and pre-pressed at 100 MPa and 25° C. for 10 seconds. Finally, the stack was placed in a flat uniaxial press and pressed at a pressing pressure of 200 MPa and a pressing temperature of 120° C. for 1 minute. Thus, the all-solid battery of Example 1 was obtained.
[0113] 《Example 2》
[0114] The negative electrode active material layer formed in the same manner as in Example 1 was stacked on the solid electrolyte layer, and lithium was used as the counter electrode, and a charge and discharge test was performed 200 times under the condition of 3.17 V to 4.16 V. Then, the negative electrode active material layer was taken out, and the negative electrode active material layer, the new solid electrolyte layer, and the positive electrode active material layer were stacked in the same manner as in Example 1 to obtain the all-solid battery of Example 2.
[0115] Comparative Examples 1 to 3
[0116] All solid batteries of Comparative Examples 1 to 3 were obtained in the same manner as in Example 1 except that the electrode active material particles of Comparative Synthesis Examples 1 to 3 were used in the preparation of the negative electrode composite material. The serial number of each Comparative Example corresponds to the serial number of the Comparative Synthesis Example.
[0117] "evaluate"
[0118] <Photographing of cross-sectional TEM images of electrode active material particles and quantification of each silicon portion>
[0119] The cross section of the electrode active material particle of Example 1 was photographed using TEM. In addition, the silicon inclusion compound part and the amorphous silicon part in the electrode active material particle were quantified using ASTAR attached to TEM. Specifically, ASTAR from Nanomegas was used to continuously collect diffraction patterns while scanning the sample with an electron beam probe, thereby quantifying each silicon part.
[0120] <Measurement of ionic conductivity>
[0121] The ionic conductivity of the electrode active material particles is measured by the following method. That is, first, the electrode active material particles are pressed and a restraining pressure is applied to the obtained pressed tablet. Then, the obtained sample is kept at 25°C and the ionic conductivity is calculated by the AC impedance method. The measurement is performed using Solartron 1260 from Solartron Analytical. The measurement conditions are set to an applied voltage of 5mV and a measurement frequency range of 0.01 to 1MHz.
[0122] <Determination of the increase in restraint pressure>
[0123] The manufactured battery cell was constrained with a specified constraining pressure using a constraining fixture, and the increase in the constraining pressure when charged to 4.55V at a constant current-constant voltage at a 10-hour rate (1 / 10C) was measured. A large increase in the constraining pressure means a large amount of expansion of the active material. It should be noted that the increase in the constraining pressure is the difference between the highest and lowest values of the constraining pressure, and the values of the embodiments and comparative examples 2 and 3 are expressed as relative values when the value of comparative example 1 is set to 100.
[0124] "result"
[0125] The cross-sectional TEM image of the electrode active material particle of Example 1 is shown in Figure 1 Table 1 shows the measurement results of the ratio of the number of silicon atoms in each silicon portion, the ion conductivity of the electrode active material particles, and the increase in the confinement pressure of the battery.
[0126]
Table 1
[0127]
[0128] like Figure 1 As shown in Table 1, the electrode active material particles of Example 1 contain a silicon inclusion compound part and an amorphous silicon part in the particles. In addition, as shown in Table 1, the battery of the embodiment containing the electrode active material particles of the present disclosure has a smaller increase in the confinement pressure than the battery of the comparative example. It is believed that this is because the electrode active material particles of the present disclosure contain a silicon inclusion compound part with a high effect of suppressing the expansion rate, and the present disclosure contains an amorphous silicon part within the range disclosed, thereby increasing the ion conductivity.
Claims
1. An electrode active material particle comprising a silicon inclusion compound portion and an amorphous silicon portion and satisfying the following relationship: 0 atomic %<the number of silicon atoms in the amorphous silicon portion / (the number of silicon atoms in the amorphous silicon portion+the number of silicon atoms in the silicon inclusion compound portion)<50 atomic %.
2. The electrode active material particle according to claim 1, which satisfies the following relationship: 0 atomic %<the number of silicon atoms in the amorphous silicon portion / (the number of silicon atoms in the amorphous silicon portion+the number of silicon atoms in the silicon inclusion compound portion)≤30 atomic %. 3 . An electrode composite material comprising the electrode active material particles according to claim 1 . 4 . A lithium ion battery comprising an electrode active material layer, wherein the electrode active material layer contains the electrode composite material according to claim 3 .
Citation Information
Patent Citations
Active material, negative electrode layer, battery and these manufacturing methods
JP2021158003A